Transformational Leadership of Tuan Guru: A Local Wisdom Approach to Preventing Bullying in Pesantren - Satriah Satriah; Prosmala Hadisaputra (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bullying in Islamic boarding schools (pesantren) poses serious psychological, social, and academic risks for students. Despite their strong moral frameworks, pesantren remain vulnerable to hierarchical practices that can perpetuate bullying. Transformational leadership grounded in local wisdom offers a potential strategy for fostering a safe and supportive environment. This study explored the transformational leadership strategies of the tuan guru at Pondok Pesantren Selaparang, West Lombok, in preventing bullying. A qualitative case study design was employed, using in-depth interviews, observations, and document analysis. Eight key informants—including the tuan guru, madrasa head, dormitory supervisor, teachers, students, and parents—provided diverse perspectives on leadership practices within the pesantren. Findings reveal that the tuan guru integrates Sasak local wisdom, including gotong royong (mutual cooperation), tolerance, and traditional practices such as Rowah, Nyunatan, Khataman, Nyongkolan, and Sorong Serah Aji Krama. These practices foster solidarity, mutual respect, and social harmony among students. Senior-junior mentoring systems strengthen supportive relationships and instil social responsibility, while a restorative approach to conflict resolution focuses on repairing relationships rather than punitive measures. Parental and community involvement further reinforces moral values beyond the school environment. The study highlights a culturally grounded transformational leadership model that effectively reduces bullying and builds students’ moral character. This hybrid approach—combining leadership principles with local wisdom—offers a replicable framework for other religious education institutions. The findings suggest the need for leadership training programs and further research to test the scalability of this model in diverse cultural contexts.